'Positive' economics and policy objectives - Hutchison, T. W. (London: George Allen & Unwin, 1964)
In this text, the concept of positive economics is examined in two directions: firstly, by surveying the treatment of the normative-positive distinction in the history of economic thought; and secondly, by tracing the sources and roles of value judgments and bias in economics. Turning to policy objectives, the book then presents an historical review of the objectives of economic policies. Finally, the formulation of policy objectives is discussed along with the contribution of welfare analysis.
Includes bibliographical references: p. 198-199 and index.
rpm 18/10/2017
Loans
Keywords: Economics